Letting kids play their CARDs (Comfort, Ask, Relax, Distract) to help cope with needle-related fear and pain: Results from user testing. Issue 52 (12th December 2022) - Taddio, Anna; Ilersich, Anthony N.T.; Bucci, Lucie; McMurtry, C. Meghan; Gudzak, Victoria; Ipp, Moshe; Zita, Tina; Tharmarajah, Shenthuraan; MacDonald, Noni
Highlights: Most children are afraid of needles and report fear or pain as the worst part of vaccination. We developed a new web-based game to educate children about fear and pain coping strategies. In the game, children learn about CARD (Comfort Ask Relax Distract), an evidence-based framework. Parents and children liked the game, learned coping strategies, and planned to use them in future. Abstract: This study examined perceptions of children and parents about a new web-based CARD (C omfort, A sk, R elax, D istract) game that teaches children how to cope with needle-related pain and fear. A convenience sample of 15 child-parent dyads (children, 6–12 years) participated. Children played the game on a handheld device while being virtually monitored. Activity tracking revealed most children engaged with multiple components. Children reported they understood the game, it was easy to play, they learned coping strategies and believed they could implement them. Children reported lower fear of needles after playing. Parents liked the simplicity and variety of game activities. Most children and parents reported they would use the game or its coping strategies for future needles and would recommend the game. In summary, children and parents found the CARD web game acceptable and appropriate. Future studies can evaluate its effectiveness when integrated into upcoming needle procedures like COVID-19 vaccinations.